MANAGEMENT EMPOWERMENT IN EFFORTS TO INCREASE PATIENT SATISFACTION AT SEMBIRING DELI TUA GENERAL HOSPITAL - Layari Tarigan; Andreais Boffil Cholilullah (JURNAL PENGMAS KESTRA (JPK), 2022)
The hospital is a social organization that is engaged in health and is able to provide disease healing and disease prevention services to the community in accordance with the expectations of the WHO (World Health Organization). Management is basically an activity that requires knowledge, art, use and implementation of activities to achieve a successful goal. Satisfaction is a view of one's happiness as well as one's disappointment with the comparison of a thought with a fruitful result or production. Community Service (PkM) aims to improve patient satisfaction. The method of implementing this PkM activity begins with collecting data on the number of unit heads in all rooms at Sembiring Deli Tua General Hospital, then making direct observations to all room units and providing socialization and education to all room unit heads. From the results of the PkM, the participant's score before the socialization activity was carried out was 60 and the lowest score was 30 with an average value of 50. After the socialization activity the highest score was 100 and the lowest score was 70 with an average value of 90. Based on the results of the PkM regarding the level of satisfaction Before socialization was carried out to all heads of the room unit, there were 16 patients who were satisfied and 14 people who felt dissatisfied. While the level of patient satisfaction after being socialized to all heads of the room unit there were 27 patients who were satisfied and only 3 patients who were not satisfied.